Climate change and human activity impacts on future flood risk in the Pearl River Delta based on the MaxEnt model - Zuo, Daxing; Wu, Chunyi; Zheng, Yanhui; Chen, Xiaohong; Wang, Lina (Frontiers in Earth Science, 2023)
In the background of global climate change and rapid urbanization, extreme climate events are frequent, and highly urbanized areas flooding problems are becoming increasingly prominent. It becomes important to develop qualitative scenario storylines to assess future flooding risk in a changing environment over the highly urbanized areas. In this study, the future (2030-2050) flood risk in the Pearl River Delta (PRD) region of China was assessed based on the MaxEnt model. We have developed four future scenarios under different emission conditions based on the representative concentration pathways (RCPs) and the shared socio-economic pathways (SSPs). The MaxEnt model was trained using flood hazard sample point data and flood risk indicators and excellent accuracy was obtained. We analyzed the influencing factors of flood risk and predicted the flood risk of the PRD under four future scenarios. According to the results, there was a significant increase in the size and proportion of high flood risk areas in most scenarios. Flood risk under scenario SSP5-RCP8.5 was the most serious in the future. Population density (POPD) and Gross domestic product density (GDPD) had the highest explanatory power for flood risk. This study predicted the changes of flood risk under the combined influence of climate change and human activities, and hoped to provide a reference for future planning and disaster mitigation construction in PRD cities.